Compter l’argent qui circule en barils : Les capitaux anglais dans les anciens Pays-Bas durant la campagne diplomatique et militaire d’Édouard IerPlantagenêt contre Philippe Le Bel (1294-1297) - David Kusman (Clio@Themis)
How does money circulate in war times, and which risks and financial fees do we have to consider ? At the end of the thirteenth century, Edward I, king of England is at war with the king of France. Edward I will pay his continental allies, among the Low Countries princes, with thousands and thousands sterling pounds each time. With this research, we aim to shed light on the costs of protecting, for the prince, the foreign money circulating within his territory. We study as well the evolution of the right of safe-conduct during war times. We conclude on a positive role of war which acted as a stimulus to the construction of this safe-conduct right